Highly Selective Ionic Transport through Subnanometer Pores in Polymer Films. (1st July 2016) - Wen, Qi; Yan, Dongxiao; Liu, Feng; Wang, Mao; Ling, Yun; Wang, Pengfei; Kluth, Patrick; Schauries, Daniel; Trautmann, Christina; Apel, Pavel; Guo, Wei; Xiao, Guoqing; et al.
Abstract : Novel transport phenomena through nanopores are expected to emerge as their diameters approach subnanometer scales. However, it has been challenging to explore such a regime experimentally. Here, this study reports on polymer subnanometer pores exhibiting unique selective ionic transport. 12 μm long, parallel oriented polymer nanopores are fabricated in polyethylene terephthalate (PET) films by irradiation with GeV heavy ions and subsequent 3 h exposure to UV radiation. These nanopores show ionic transport selectivity spanning more than 6 orders of magnitude: the order of the transport rate is Li + >Na + >K + >Cs + >>Mg 2+ >Ca 2+ >Ba 2+, and heavy metal ions such as Cd 2+ and anions are blocked. The transport can be switched off with a sharp transition by decreasing the pH value of the electrolyte. Structural measurements and molecular dynamics simulations suggest that the ionic transport is attributed to negatively charged nanopores with pore radii of ≈0.3 nm, and the selectivity is associated with the dehydration effect. Abstract : Negatively charged subnanometer pores are fabricated in polymer films by GeV heavy ions irradiation without chemical etching. Their selective ionic transport rates span more than 6 orders of magnitude and follow the rarely observed Eisenman sequence XI.